Sistem Informasi Pengelolaan Kegiatan Karang Taruna (SIPEKATAR) Naralatu Agantuka Berbasis Website - Paulus Tofan Rapiyanta; Tali Buana Pamungkas Regen (Retii, 2019)
Naralatu Agantuka is a youth organization in Tlogo Village, Prambanan District, Klaten Regency, Central Java. Disclosure of information about the activities of the Naralatu Agantuka youth organization is still conducted conventionally. Today, disclosure of information is carried out through leaflets posted on bulletin boards, through Social media and by telephone or by direct conversation. These problems were solved by developt a website for information about the management of the youth organization (SIPEKATAR). The purpose of making this system is to facilitate the members of the youth organization in obtaining information about the activities of the youth organization. Data collection techniques use observation methods, interview methods, and literature research. While the software development approach used for website creation is Rapid Application Development (RAD). For software design, interfaces must be the first design, and then Entity Relationship Diagrams (ERD) and Logical Record Structure (LRS). For check this website use Black Box Testing. Based on the tests, it can be concluded that the Management Information System of Naralatu Agantuka a Youth Organisation (SIPEKATAR) has been operating as supposed with valid result. This website can make it easier for members of the youth organization to obtain information on activities and make it easier for management to manage youth activities.